Optical and Structural Properties of Tb DOPED Cds Nanoparticles - Jindal, Shivani (My University, 2015)
Cadmium Sulphide (CdS) is one of the most important group II–VI based semiconductor with a direct bandgap of 2.42eV at room temperature. CdS:Tb nanoparticles have been synthesized by using Hydrothermal technique. The crystal structure and the average crystallite size of synthesized nanoparticles have been calculated by using X-Ray diffraction pattern. The morphology of nanoparticles has been studied through SEM images. The elemental analysis has been carried out by EDAX spectroscopy. The band gap of synthesized nanoparticles has been calculated by UV-Visible absorption spectra. Room temperature PL studies have been carried out to study the emission spectra of synthesized nanoparticles.
M.Sc. (Physics)
Keywords: CdS nanoparticles; Tb-doped nanoparticles; physics; nano particles; SPMS